Panorama dos Estudos de Jogos no Brasil (2019-2023) : abordagens teórico-metodológicas a partir da Comunicação - Silva, Soraya Madeira da (2025)
The main objective of this thesis is to provide an overview of Game Studies in Brazil, focusing on the field of Communication, based on theses defended between 2019 and 2023. It aims to identify their main methodological and conceptual trends and understand how digital games have been treated as an academic research object. The initial chapters seek to define games and digital games through the adaptation of mappings by Juul (2019) and Salen and Zimmerman (2012a); present a brief overview of studies about games, including the pioneering authors Huizinga (2019) and Caillois (2017); define the field of Game Studies (Fragoso; Amaro, 2018; Freyermuth, 2015); understand the language of games through the sound, visual, and verbal matrices (Santaella, 2019); and identify the characteristics of digital games as media (Parikka, 2021; Ávila, 2020; Perani, 2016; Perani, 2014; Bolter; Grusin, 2000; Postali; Iuama, 2021). The research employs a combined methodology based on the methods of Fragoso (et al., 2015; et al., 2016; 2017a) and Moreira (2023), using systematic review and Bardin's content analysis (2020). The corpus includes 26 theses selected using strict inclusion and exclusion criteria. Among the main findings, the interdisciplinarity of the field stands out, which uses concepts and methods from fields such as Semiotics, Narratology, Design, and Phenomenology, while also incorporating specific methodologies for game analysis. The data highlight a growing consolidation of Game Studies as an academic field in Brazil, emphasizing the playful interaction, aesthetic experience, and cultural aspects of digital games.